Al Zarnuji’s Learning Principles in the Malaysian National Education Philosophy: An Integrated Model of Islamic Spiritual Intelligence - Tengku Mohd Farid Tengku Abdul Aziz; Nurul Iman Ahmad Bukhari; Muhammad Luqman Ibnul Hakim Mohd Saad (Journal of Human Development and Communication (JoHDeC), 2025)
One of the underlying principles of the Malaysia National Education Philosophy (NEP) is to produce well-balanced human capital in terms of physical, intellectual, emotional and spiritual aspects. However, of all human intelligence, the concept of spiritual intelligence is less discussed, particularly in the educational context. In this diverse world of complex cultural and religious composition, the spiritual elements in NEP are being separated and narrowed down to religious and moral studies. Among the rising issues regarding morality and ethics pertaining to the Malaysian educational system, the aspect of spiritual intelligence cannot be further neglected. The challenge for Muslims is to have further interpretation from a new fresh outlook of Islamic spiritual intelligence perspective. Thus, this study proposes an Integrated Islamic Spiritual Intelligence (ISI) model in accordance to the Malaysia National Education Philosophy with the aim to provide an integrated view on ISI based on Al Zarnuji’s Learning Principles (Ta‘līm al-Muta‘allim).